A PHYSICAL AND NUTRITIONAL QUALITY DETERMINATION OF THE DATE OF HARVEST OF THE COWPEA (CV. IFE BROWN) POD AS A VEGETABLE - ADEGOROYE , ADEGOKE S.; OMOLE, ABIOLA E. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
An evaluation study of the cowpea as a green vegetable was conducted by determining the physical and nutritional quality changes or a cowpea cultivar (cv. Ife Brown) during pod development, with a view to finding a solution to the incessant post-maturity pest and fungal attack of the pod in the humid tropics. The results show that pod length continued to increase till 20 days after anthesis (DAA). However, maximum pod diameter, seed diameter, pod wall thickness and a corresponding minimum void space were attained at 14 DAA. Noticeable change pod colour occurred in DAA the same time that the pod became slightly stringy. Maximum ascorbic acid content was obtained at 11 DAA while the minimum level of protein per fresh weight occurred at 15 DAA. Crude fibre content also sharply after 15 DAA. Taste panel investigation results indicated a significant preference for cowpea pods harvested 11-13 DAA compared to a commercial variety of green beans.